The ‘Real Without Law’ in Psychoanalysis and Neurosciences - Aguiar, Adriano (Frontiers in Psychology, 2018)
The article discusses some of Lacan’s concepts on the relation between psychoanalysis and science. The difference that Lacan states between the real for science, which would be entirely governed by laws, and the real for psychoanalysis - a ‘real without law’ - risk to lead to a irreductible separation between the two fields. However, as the article shows, that separation between psychoanalysis and science is not the position defended by Freud and Lacan. Indeed the latest discoveries in the field of neurosciences challenge the traditional conception of the real for science, bringing it closer to the real ‘without law’ that characterizes psychoanalysis. Conceiving the real for science as a real that is opened to contingencies and not entirely governed by laws, is the first necessary step for a new alliance between psychoanalysis and science.